2016
DOI: 10.1074/jbc.m116.718478
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That G-quadruplex DNA Accumulates in the Cytoplasm and Participates in Stress Granule Assembly in Response to Oxidative Stress

Abstract: Cells engage numerous signaling pathways in response to oxidative stress that together repair macromolecular damage or direct the cell toward apoptosis. As a result of DNA damage, mitochondrial DNA or nuclear DNA has been shown to enter the cytoplasm where it binds to "DNA sensors," which in turn initiate signaling cascades. Here we report data that support a novel signaling pathway in response to oxidative stress mediated by specific guanine-rich sequences that can fold into G-quadruplex DNA (G4DNA). In respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 116 publications
(147 reference statements)
3
76
0
Order By: Relevance
“…Indeed, many natural proteins have been identified that interact with G4s (see G4 Interacting Proteins Database, http://bsbe.iiti.ac.in/bsbe/ipdb/) [61]. The identification of G4 associated proteins has mostly relied on affinity proteomics experiments employing RNA and DNA G4 oligomers as baits to isolate G4 interactors from cellular extracts [62][63][64][65]. Other approaches involve computational analysis of genomic protein binding sites to assess the enrichment of predicted G4 motifs within these binding sites [54,66], or meta-analysis, in which shared structural features of G4-binding protein domains were compared to predict new putative G4 interactors [67,68].…”
Section: Natural G4-binding Proteinsmentioning
confidence: 99%
“…Indeed, many natural proteins have been identified that interact with G4s (see G4 Interacting Proteins Database, http://bsbe.iiti.ac.in/bsbe/ipdb/) [61]. The identification of G4 associated proteins has mostly relied on affinity proteomics experiments employing RNA and DNA G4 oligomers as baits to isolate G4 interactors from cellular extracts [62][63][64][65]. Other approaches involve computational analysis of genomic protein binding sites to assess the enrichment of predicted G4 motifs within these binding sites [54,66], or meta-analysis, in which shared structural features of G4-binding protein domains were compared to predict new putative G4 interactors [67,68].…”
Section: Natural G4-binding Proteinsmentioning
confidence: 99%
“…Very recently, the Raney lab showed that G4 DNA accumulates in the cytoplasm of human cells exposed to the DNA oxidizing agent H 2 O 2 and participates in the assembly of stress granules [129]. This discovery raises the question if a deficiency in a nuclear or cytosolic G4 resolving helicase or G4 binding protein might modulate the oxidative stress response via the newly discovered G4-induced stress granule formation pathway.…”
Section: Oxidative Stress G4-forming Sequences and Potential Involvmentioning
confidence: 99%
“…This discovery raises the question if a deficiency in a nuclear or cytosolic G4 resolving helicase or G4 binding protein might modulate the oxidative stress response via the newly discovered G4-induced stress granule formation pathway. Indeed, Byrd et al identified the most abundant human G4-resolving helicase DHX36/RHAU/G4R1 helicase [130] using G4 DNA as bait in the pull-down assay using human cell lysates [129]. Further studies in this exciting area are warranted given the interest in G4 nucleic acids as a potential molecular target in cancer therapies [131, 132].…”
Section: Oxidative Stress G4-forming Sequences and Potential Involvmentioning
confidence: 99%
“…Translation elongation or termination are unlikely to be affected by DHX36 considering that only a minority of DHX36 is found on polysomes and that we do not find a pile-up of ribosomes close to the stop codons or in the 3’ UTR of target mRNAs. This indicates that the additional target mRNA in DHX36 KO cells is not translation competent, either due to decreased efficiency of translation initiation, or by sequestration of these RNAs into granules, such as P-bodies or stress granules, which are known to recruit G4 structures and function as storage for untranslated mRNA (Byrd et al, 2016; ChalupnĂ­kovĂĄ et al, 2008; Hubstenberger et al, 2017; Ivanov et al, 2014). DHX36 might impact translational output by modifying the levels of translatable target mRNAs.…”
Section: Discussionmentioning
confidence: 99%